"Uncontrolled sovkhoism": administering reindeer husbandry in the Russian far north (Kola Peninsula). (3rd July 2018) - Konstantinov, Yulian; Istomin, Kirill; Ryzhkova, Inna; Mitina, Yulia
ABSTRACT: Sovkhoism is a world-view extolling the virtues of the Soviet Farm ( sovkhoz ) as the foundation of a grassroots-friendly socio-economy. We discuss the post-Soviet "uncontrolled" state of sovkhoism in Murmansk Region reindeer husbandry. We argue that the key descriptor of the state of reindeer husbandry: the head-count ( pogolovye ) is often an arbitrary figure in a subsidy-producing narrative. In it, overall head-count numbers tend to be inflated, while a critical differentiation between the categories of personal vs. private reindeer is obliterated. Further, the head-count/subsidies narrative reproduces the central features of Soviet-era socio-economy of sovkhoism. The present, post-Soviet state of this process, we discuss as lacking previously existing mechanism of outside control. We conclude that reindeer husbandry in the Russian Far North is in need of returning to a relatively controlled state by the introduction of independent and publicly transparent controlling agency. Non-sovkhoist, "fully private" development is seen to be unrealistic at this stage, apart from isolated cases in the region concerned.